Dissolution behaviour and activation of selenium in phosphonium based ionic liquids - Zhang, Tao; Schwedtmann, Kai; Weigand, Jan J.; Doert, Thomas; Ruck, Michael (Chemical Communications, 2017)
The dissolution behaviour of grey selenium in phosphonium based ionic liquids (ILs) has been investigated for the first time by 31P and 77Se nuclear magnetic resonance (NMR) experiments. The investigations evidence the formation of trialkylphosphane selenides which can serve as a selenium reservoir in the subsequent formation of metal selenides.
CRIS-Team Scopus Importer:2022-04-14